Application of Innovations in the Sector of Accommodation Service (Laisvalaikio tyrimai, 2018)
Research background. During these days the innovations are a more and more used definition in the business, especially in the market research, human resource management, new products and service development, etc. Frequently innovations are related with the application of new technology and new ideas as well as creation of new methods. Even more, innovations are related with the development of existing processes and products (Bigliardi, Dormio, 2009). Innovations are important in the sector of tourism industry, which is expanding every time combining more and more different areas of business. According to Melnikas (2011), discontent and necessity of changes are some persuasive factors to begin an activity of innovation. Thus, it could be the reason for the application of innovations in the sector of accommodation service to become essential. Importance of innovations is discussed pretty widely in the scientific literature (Bigliardi, Dormio, 2009; Hall, Williams, 2008; Inauen, Schenker-Wicki, 2011; Notaro et al., 2012), but innovations in tourism sector have been discussed only recently (Nagy, 2012; Ravar, Iorgulescu, 2013). This article is relevant because application of innovations in the sector of accommodation service is not enough discussed in Lithuania as it is done by some foreign scientists (Sundbo et al., 2007; Hall et al., 2008; Ravar, Iorgulescu, 2013). The object of the research is innovations in the sector of accommodation service, and the aim is to determine the activeness of innovations’ application in the sector of an accommodation service. Research methods. This article deals with the application of innovations in the sector of accommodation service using the method of scientific literature analyses and quantitative empirical research – the method questionnaire survey. The research respondents were the employees of Kaunas city organizations of accommodation service. The author of this article is grateful to her student Martynas Bruzas who collected 270 filled in questionnaires. Results and discussion. Innovations are the most frequently described as an application of technologies creating new products, new services, and new processes of activity in the market. Innovations are combined with technological changes in the products, services and their creation processes. The research results revealed that services of accommodation business were restricted by just using electronic mail, the electronic page of business and electronic page of socialization. The research results revealed that services of accommodation business performed just slight changes of innovations according to some novelties in the market. On the other hand, employees of these organizations were enough sure that their organizations were applying innovations, but at the same time they thought that innovations could be more combined with the qualifications of organizations’ employees. Conclusions. According to research results, we suggest that most Kaunas city accommodation services presume that they are active in the application of innovations, but there were only some technological changes of innovations. The research results revealed that usually innovations were related to IT programs of accommodation service, wireless internet, telephone, television, touch tabs, room infrastructure and the systems of reservations.Keywords: innovations, innovations of accommodation sector, development.